Identifying stack-driven indoor environmental problems and associated pressure difference in high-rise residential buildings: Airflow noise and draft. (15th January 2020) - Yoon, Sungmin; Song, Doosam; Kim, Jaehun; Kim, Joowook; Lim, Hyunwoo; Koo, Junemo
Abstract: Building airflow is a main factor in indoor air and environmental qualities. In particular, stack-induced airflow can cause indoor environmental problems in high-rise buildings over the winter due to the strong driving force (pressure difference). The goal of this study was to identify the actual characteristics of stack-driven environmental problems in real high-rise residential buildings through a field survey and airflow simulation. We collected the actual resident complaints (140 cases) raised in six high-rise residential buildings in South Korea during three years. The most frequent complaints were airflow noise and drafts at residential entrance doors. Then, by a calibrated airflow simulation, we identified the unknown pressure differences that caused these two problems. Based on the pressure differences, this study could determine problem occurrence rates for noise and drafts depending on given pressure differences. Apart from the existing allowable or reference pressure difference (50 Pa) across doors suggested by ASHRAE and European standards (EN 12101-6), which is related to emergency escape, three reference levels were suggested: (1) tight: 25 Pa, (2) normal: 40 Pa, and (3) loose: 65 Pa. These values were intended to be used as the reference in predicting or solving the stack-driven problems. Finally, we successfully predicted the frequency of these problem occurrences over the winter in a target building, using a coupled airflow and thermal simulation. These results showed the importance of the newly suggested references, 25 Pa or 40 Pa rather than 50 Pa, in identifying the stack-driven airflow noise and draft. Highlights: Airflow noise and draft were found to be the most common stack problems. An analysis method was developed to estimate the pressure differences causing problems. Three levels of reference pressure differences were suggested for the noise and draft problems. Based on each reference, the frequency of problem occurrence was predicted over an entire winter.